Preferensi Habitat dan Distribusi Spasial Yuwana Rajungan (Portunus pelagicus) di Perairan Pesisir Lampung Timur, Provinsi Lampung - Muhamad Radifa; Yusli Wardiatno; Charles P.H. Simanjuntak; Zairion Zairion (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Information on habitat preferences of the blue swimming crab (BSC) juvenile and its spatial distribution is one of the factors behind the successfulness of its sustainable management. This information is needed to provide input for management strategy by considering juvenile crabs and their habitat as important aspect. The purpose of this study is to elucidate habitat preferences, abundance and biomass distribution of BSC juvenile in the east Lampung coastal waters. The research was conducted in September-October 2018, which was located in east Lampung coastal waters, Province Lampung. Spatial distribution through estimation of abundance and biomass of BSC juvenile were relatively high and concentrated in the Gambas and Wako regions at stratification of 2-4 miles from the coastline. The BSC juvenile does not appear to have a high preference to the Kuala Penet coastal habitat condition; it is considered because of low value of abundance, biomass, and Habitat suitability index (HSI). The value of HSI in the Kuala Penet Coastal region is also lower than other locations due to abiotic and biotic factors for supporting the crabs at juvenile stage.